Studies in symbolic interaction. Vol. 29 - Denzin, Norman K. (Greenwich, CT : JAI, 2007)
Volume 29 of "Studies in Symbolic Interaction" honors Ron Pelias' contributions to symbolic interaction and performance studies. The work of Patricia Ticineto Clough is also honored. New theoretical developments in the areas of race, identity, politics and authenticity are presented, as are performance essays interrogating mental health care, and the representations of gender and sexuality in the popular HBO series, "Sex in the City". It honors the work of Ron Pelias and Patricia Ticineto Clough and features a performance essay that discusses representations of gender and ethnicity in HBO's "Sex and the City".
Description based on print version record.
Keywords: Symbolic interactionism; Social interaction; Social, group or collective psychology; Social Science -- Sociology -- General